2018 IEEE Global Conference on Signal and Information Processing (GlobalSIP) 2018
DOI: 10.1109/globalsip.2018.8646375
|View full text |Cite
|
Sign up to set email alerts
|

Polar Feature Based Deep Architectures for Automatic Modulation Classification Considering Channel Fading

Abstract: To develop intelligent receivers, automatic modulation classification (AMC) plays an important role for better spectrum utilization. The emerging deep learning (DL) technique has received much attention in AMC due to its superior performance in classifying data with deep structure. In this work, a novel polar-based deep learning architecture with channel compensation network (CCN) is proposed. Our test results show that learning features from polar domain ( -) can improve recognition accuracy by 5% and reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 13 publications
(19 reference statements)
0
19
0
Order By: Relevance
“…Teng et al [5] extend their previous work in [91] and proposed an accumulated polar feature-based DL with a channel compensation mechanism. In [91], they have shown that learning features from polar coordinates, which can be obtained from Cartesian coordinates, can achieve higher recognition accuracy. Then in [5], they add a new temporal axis to accumulate historical information of symbols in such dimension.…”
Section: D: Classification Using Other Inputsmentioning
confidence: 83%
See 1 more Smart Citation
“…Teng et al [5] extend their previous work in [91] and proposed an accumulated polar feature-based DL with a channel compensation mechanism. In [91], they have shown that learning features from polar coordinates, which can be obtained from Cartesian coordinates, can achieve higher recognition accuracy. Then in [5], they add a new temporal axis to accumulate historical information of symbols in such dimension.…”
Section: D: Classification Using Other Inputsmentioning
confidence: 83%
“…Two mechanisms for online retraining were introduced to deal with the timevarying fading channel while having lower transmission and retraining overhead. The model reported in [91] was used as a benchmark. Results revealed that the proposed method can reduce the offline training overhead by about 190 times compared to [91] and, therefore, provide better efficiency and accuracy.…”
Section: D: Classification Using Other Inputsmentioning
confidence: 99%
“…It is measured by computing the ratio of the correctly estimated modulation scheme to the original modulation scheme of the received signal. It can be approximated as follows: (32) where 1 represents the true positive, 2 represents the true negative, ℱ 1 represents the false positive, and ℱ 2 represents the false negative. As the work is about multi-class classification, we construct confusion matrix by considering actual class and predicted class for all classes.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, the performance of the AEs decreased for a large-scale dataset due to high computation processes. Chieh-Fang et al [32] exploited a channel compensation network (CCN) to detect the modulation type of the signal. Polar features were learnt through polar transform.…”
Section: Amc With MLmentioning
confidence: 99%
“…With more and more revolutionary breakthroughs in the fields of computer vision and natural language processing, machine learning-assisted communication systems have gradually attracted attention in recent years [1]- [2]. For example, a powerful modulation classifier is proposed in [3]- [5] by taking advantages of convolutional neural networks. For channel decoding, the authors in [6]- [8] propose neural network-based decoders for BCH code and polar code, which have better performance and faster convergence.…”
Section: Introductionmentioning
confidence: 99%